The Rational vs. Behavioral Approaches to Strategy Thinking - Seckin Celik, Tutku (International Journal of Contemporary Economics and Administrative Sciences, 2019)
Strategic thinking in management literature dates back to 1960s. From these days forward, strategy has been defined and conceptualized in many different ways. As a result different schools of thoughts and diverge approaches have been detected, and several classifications have been made. Two fundamental approaches to strategy are rational and behavioral strategic thinking. In this article, the meaning of strategy in general, and the viewpoints of rational and behavioral thinking will be discussed deeply while comparing them. Although classical rational planning approach has many drawbacks and behavioral approach have risen as a criticism against it, both are valuable and using them together leads to more comprehensive solutions to strategic problems.